Upcoming treatments for morphea - Dan Wenzel; Nazgol‐Sadat Haddadi; Khashayar Afshari; Jillian M. Richmond; Mehdi Rashighi (Immunity, Inflammation and Disease, 2021)
Abstract Morphea (localized scleroderma) is a rare autoimmune connective tissue disease with variable clinical presentations, with an annual incidence of 0.4–2.7 cases per 100,000. Morphea occurs most frequently in children aged 2–14 years, and the disease exhibits a female predominance. Insights into morphea pathogenesis are often extrapolated from studies of systemic sclerosis due to their similar skin histopathologic features; however, clinically they are two distinct diseases as evidenced by different demographics, clinical features, disease course and prognosis. An interplay between genetic factors, epigenetic modifications, immune and vascular dysfunction, along with environmental hits are considered as the main contributors to morphea pathogenesis. In this review, we describe potential new therapies for morphea based on both preclinical evidence and ongoing clinical trials. We focus on different classes of therapeutics, including antifibrotic, anti‐inflammatory, cellular and gene therapy, and antisenolytic approaches, and how these target different aspects of disease pathogenesis.